ГЕОГРАФИЯ САБАҚЛАРЫНДА МАШҚАЛАЛЫ ОҚЫТЫЎДЫҢ ҚОЛЛАНЫЛЫЎЫ - Гаипова, Р.Т.; Тўраев, Б.; Шәрибаев, А.; Орынбаева, А. (FAN va JAMIYAT, 2018)
The article deals with the issues and methods of problem-based learning at Geography lessons. Therefore, the author studies problem based teaching and the causes of problem situations and their importance in the learning process.